MITIGATION STRATEGIES TO IMPROVE SAFETY CONDITIONS AT FUEL STATIONS - Mirza, Munir; Kutty, S.R.M.; Khamidi, M. Faris; Shariff, Azmi Mohd (2010)
Injury free work environment is an essential element for any successful project. Better safety performances can be achieved only if safety matters priority at all stages of project addressed adequately. Concrete efforts of owners, contractors, sub contractors and designers are equally important at different levels of project. To control accidents and injuries on every project requires different methods and practices. Although same strategies can be applied, it requires modifications as per objectives & targets and organizational needs. It is necessary to develop such strategies that can help to increase safety considerations at project site. Past safety studies investigated various methods to improve safety statistics but it still contain more room for improvement. Fuel stations are considered to be the high risk hazardous places within the city environment. Fire, falls, vehicle accidents, electrocutions, robbery and snakebites are most commonly occurring hazardous conditions at fuel stations. This paper will present the application of Mitigation Strategies to reduce near misses occurrences at fuel stations. Near misses data collected in different trades such as maintenance, carelessness, housekeeping, mechanical fault and electrical fault. Mitigation strategies prepared based upon safety statistics. Data collected with these application and mentionable improvement noticed. With application of mitigation strategies available resources can be utilized more appropriately. In case of unavailability, requirements can be highlighted for procurement.